Gender Equality in Education: Progress and Barriers in Secondary School Enrollment - Amina Otieno; David Mwangi; Peter Kariuki (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study examines the progress made and the ongoing barriers to achieving gender equality in secondary school enrollment worldwide, with a focus on countries with high gender disparities. By analyzing policies, cultural factors, and economic barriers that hinder girls' access to secondary education, the research highlights the complex challenges that persist despite improvements in global enrollment rates for girls. Findings suggest that while progress has been made, there are still significant obstacles, such as child marriage, cultural expectations, and lack of educational resources, which prevent many girls from completing secondary education.